Interspeech 2019 2019
DOI: 10.21437/interspeech.2019-1799
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Hierarchical Attention Neural Network for Detecting AD

Abstract: Picture description tasks are used for the detection of cognitive decline associated with Alzheimer's disease (AD). Recent years have seen work on automatic AD detection in picture descriptions based on acoustic and word-based analysis of the speech. These methods have shown some success but lack an ability to capture any higher level effects of cognitive decline on the patient's language. In this paper, we propose a novel model that encompasses both the hierarchical and sequential structure of the description… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 17 publications
1
44
1
Order By: Relevance
“…Another recent attempt to address the use of neural networks for detecting dementia is the recent work of Pan et al [49]. They have proposed a hierarchical bidirectional neural network induced with an attention mechanism for extracting different levels of features.…”
Section: Related Workmentioning
confidence: 99%
“…Another recent attempt to address the use of neural networks for detecting dementia is the recent work of Pan et al [49]. They have proposed a hierarchical bidirectional neural network induced with an attention mechanism for extracting different levels of features.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, automatic approaches to analysing a person's speech and language have gained traction. Language-based analysis is mostly carried out on either the manual or automatic transcripts [4,5], whereas speechbased analysis would normally be based on the acoustic signal [6][7][8][9][10][11]. In both cases, the performance of a typical classification pipeline is highly dependent on the quality of the front-end features.…”
Section: Introductionmentioning
confidence: 99%
“…In [20], it was found that combining CNNs, LSTMs, and DNNs for speech processing in a unified architecture allowed for the exploitation of their complementary natures. The attention mechanism has lately been used in different fields and achieved a great deal of success [4,21,22]. The main idea behind the attention mechanism is to apply a higher attention weight to the more critical parts of the input for classification.…”
Section: Introductionmentioning
confidence: 99%
“…Further improvements are seen when combining with the rhythm-inspired features. (3) Applying the proposed technique to our linguistic-based system proposed in [22] also improves that system. (4) Finally, combining our acoustic and linguistic systems achieves a further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, RNNs are good at capturing the temporal evolution of input signals and model the sequence information [23], which is suitable for the acoustic and rhythm feature modelling. The attention mechanism has lately been used in different fields and achieved a great deal of success [22,24]. The main idea behind the attention mechanism is applying a higher attention weight to the more critical parts of the input for classification.…”
Section: Introductionmentioning
confidence: 99%